2023
DOI: 10.1177/18479790231160857
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation for cold chain management in freight forwarding industry

Abstract: During the pandemic, the attention and demand for cold chain increased owing to considerable use of low-temperature logistics in transporting perishable goods and vaccines. To ensure the shipping performance for reduced damage, logistics companies are required to track continually and repetitively the status of shipments daily. However, typing various air waybills for searching the shipping status is a cause of frequent errors. Also, tracking the shipping status is labor-intensive, resource intensive, ineffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Lam, H-Y [41] analyzed the digital transformation for cold chain management in the freight forwarding industry and concluded that robotic process automation significantly reduced data processing time. Through the case study, the author tested and evaluated the performance of two unattended robotic process automation bots applied in a freight forwarder company to check shipment status and temperature conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lam, H-Y [41] analyzed the digital transformation for cold chain management in the freight forwarding industry and concluded that robotic process automation significantly reduced data processing time. Through the case study, the author tested and evaluated the performance of two unattended robotic process automation bots applied in a freight forwarder company to check shipment status and temperature conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It involves utilising specialised cold chain technologies, such as cold storage facilities, refrigerated vehicles, and thermal packaging, to maintain product quality, safety, and integrity from the point of origin to the final delivery to end customers (Tsang et al, 2020). The operational flow of cold chain e-fulfilment is more complex than traditional e-fulfilment processes, as it includes temperature-controlled warehousing, inventory management, order processing, picking and packing, transportation, and time-sensitive last-mile delivery (Lam & Tang, 2023;Salin & Nayga, 2003;X. Wang & Cao, 2021).…”
mentioning
confidence: 99%